LKB1 Somatic Mutations in Sporadic Tumors - Avizienyte, Egle (American Society for Investigative Pathology, 1999)
Germline mutations of LKB1/Peutz-Jeghers syndrome gene predispose carriers to hamartomatous polyposis of the gastrointestinal tract as well as to cancer of different organ systems. Although Peutz-Jeghers syndrome patients frequently present with neoplasms of the colon, stomach, small intestine, pancreas, breast, ovaries, and cervix, somatic mutations appear to be rare in the sporadic tumor types thus far studied (colorectal, gastric, testicular, and breast cancers). To evaluate whether somatic mutations of LKB1 contribute to the tumorigenesis of yet unstudied tumor types, we screened 14 cell lines and 129 tumor specimens from different cancers for a genetic defect in LKB1. Six melanoma and eight myeloma cell lines were scrutinized for LKB1 somatic mutations by genomic sequencing. No changes were found in the coding LKB1 sequence and exon/intron boundaries. Next, we analyzed 12 pancreatic, 8 gastric, 12 ovarian granulosa cell, 26 cervical, 28 lung, 24 soft tissue, and 19 renal tumors by single-strand conformational polymorphism analysis. Three changes in LKB1 coding nucleotide sequence were identified. One base pair deletion at A957 and G958 substitution by T occurred in a cervical adenocarcinoma sample, resulting in a frameshift and premature stop codon at position 335. Substitution of A581 by T occurred in a lung adenocarcinoma sample, resulting in the change of aspartic acid at position 194 to valine. A loss of another allele was detected in this sample. One silent change, C1257T, was found in a pancreatic carcinoma sample. The changes were not present in the matched normal tissue DNA samples. Our results suggest that mutational inactivation of LKB1 is a rare event in most sporadic tumor types.